High-resolution dental magnetic resonance imaging for planning palatal graft surgery: a clinical pilot study - Hilgenfeld, Tim; Kästel, Thorsten; Heil, Alexander; Rammelsberg, Peter; Heiland, Sabine; Bendszus, Martin; Schwindling, Franz Sebastian (Journal of clinical periodontology, 2018)
Aim To evaluate whether high-resolution, non-contrast-enhanced dental magnetic resonance imaging (MRI) can be used for accurate determination of palatal masticatory mucosa thickness (PMMT) and to locate the greater palatal artery (GPA). Materials and Methods In five volunteers (four males, one female; mean age 30.2 ± 0.4 years), two independent raters measured PMMT by use of dental MRI in 180 positions. For comparison, clinical bone sounding was performed. The GPA was identified in time-of-flight (TOF) angiography and MSVAT-SPACE-prototype sequence. Intra- and inter-observer agreement for MRI measurements, agreement between MRI and bone sounding were analysed by intra-class correlation coefficient (ICC) and Cohen's kappa (κ). Results Reliability of dental MRI measurements was high (intra-observer-ICC 0.962; inter-observer ICC 0.959). Agreement of MRI measurements with bone sounding was moderate (ICC 0.744), and the GPA could be identified in 60% of measurement points using the TOF-angiography alone and in 85% with additional information of the MSVAT-SPACE. Good intra-observer agreement was observed for GPA identification (κ: 0.778). Conclusion Palatal masticatory mucosa thickness measured by high-resolution, non-contrast enhanced dental MRI is comparable with that obtained by bone sounding. Dental MRI enables reliable, non-invasive and radiation-free planning of palatal tissue harvesting and can also be used for location of the GPA at 85% of measurement points, which might help reduce complications during surgery.
Accepted: 5 January 2018
Gesehen am 15.01.2020